Reconstruction of Through-and-Through Mandibular Defects with the Fibula Osteocutaneous and Lower Lateral Leg Perforator Free Flaps. Issue 1 (January 2022) - Shahzad, Farooq; Kiwanuka, Elizabeth; Marano, Andrew; Boyle, Jay; Matros, Evan
Abstract : Supplemental Digital Content is available in the text.